Hábitos de estudio y su influencia en el rendimiento académico de los estudiantes de la escuela de educación básica “Humboldt” del cantón Penipe parroquia el Altar comunidad Utuñag, período 2021- 2022. - Gaibor Camacho, Adriana Alejandra (2024)
Study habits are important because it allowed discovering the problem of the research to be carried out, with a sample in which it indicates how the students are and its influence on academic performance, which was affected by various factors that sometimes led to some difficulty in school performance. The general objective of the research is to determine the study habits and their influence on the academic performance of the students of the "Humboldt" School of Basic Education of the Canton Penipe Parroquia el Altar Community Utuñag, period 2021-2022. The methodology with an approach was used. Mixed, allowing to analyze data and to be able to state the research questions and describe the results obtained in the data interpretation process, with a non-experimental, descriptive, relational, basic research design, field study; with a study population of 42 students from fifth to seventh EGB; With data collection instruments, the Habits and Techniques Questionnaire (CHTE) and the list of student qualifications were used. Through the application of the Study Habits and Techniques Questionnaire, it was evidenced that 57.1% have a regular study habit, while 38.1% have a good study habit. However, in academic performance, 88.10% master the required learning and 11.90% reach the required learning. It is concluded that it is essential to strengthen the trust between teachers and students so that it is a comfortable place, that is, far from distracting mechanisms, favoring their better concentration, with the support of techniques to forge study habits.